Arg972 insulin receptor substrate‐1 polymorphism and risk and severity of rheumatoid arthritis. (25th November 2014) - Zhao, Hongjun; Liu, Shiqing; Long, Mei; Peng, Lijuan; Deng, Hongxiang; You, Yunhui
Abstract: Aim: To explore the association between the Arg 972 insulin receptor substrate (IRS)‐1 polymorphism (rs1801278) and the risk and disease activity/severity of rheumatoid arthritis (RA). Method: We genotyped the Arg 972 IRS‐1 polymorphism in 871 pairs of age‐, sex‐, body mass index‐, residence area‐ and current smoking status‐matched RA patients and controls. We assessed RA severity using the disease activity score of 28 joints (DAS28). Results: The AA (homozygous Arg 972 IRS‐1) and GA (heterozygous Arg 972 IRS‐1) genotypes were significantly associated with high risk of RA with or without adjustment for comorbidities ( P  < 0.001). The A allele was significantly associated with high risk of RA ( P  < 0.001). The AA genotype was significantly associated with high/severe RA activity ( P  < 0.001), while the GG genotype (wild type IRS‐1) had protective effects. Conclusion: The Arg 972 IRS‐1 polymorphism is associated with increased risk and disease activity/severity of RA, and therefore may be a potential prognostic factor for RA. This study adds novel insights into the pathogenesis of RA.